2013
DOI: 10.1093/nar/gkt345
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell paired-end genome sequencing reveals structural variation per cell cycle

Abstract: The nature and pace of genome mutation is largely unknown. Because standard methods sequence DNA from populations of cells, the genetic composition of individual cells is lost, de novo mutations in cells are concealed within the bulk signal and per cell cycle mutation rates and mechanisms remain elusive. Although single-cell genome analyses could resolve these problems, such analyses are error-prone because of whole-genome amplification (WGA) artefacts and are limited in the types of DNA mutation that can be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
131
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(140 citation statements)
references
References 50 publications
8
131
1
Order By: Relevance
“…It is important to bear in mind that these studies are based on the analysis of DNA from extractions from large numbers of cells, which only allows detection of CNVs if they are present in at least 5-10% of the cells 11,12 . In contrast, the recent development of new methods for the comprehensive study of the single cell genome [13][14][15][16] , epigenome 17 and transcriptome 18 is leading to a new understanding of cellular diversity. For instance, the study of single breast cancer cells revealed a significant number of de novo DNA copy number changes that appeared after only one cell cycle 15 and the analysis of large numbers of single cells has provided interesting insight in the evolution of genetically different cell populations within one tumour [14][15][16] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to bear in mind that these studies are based on the analysis of DNA from extractions from large numbers of cells, which only allows detection of CNVs if they are present in at least 5-10% of the cells 11,12 . In contrast, the recent development of new methods for the comprehensive study of the single cell genome [13][14][15][16] , epigenome 17 and transcriptome 18 is leading to a new understanding of cellular diversity. For instance, the study of single breast cancer cells revealed a significant number of de novo DNA copy number changes that appeared after only one cell cycle 15 and the analysis of large numbers of single cells has provided interesting insight in the evolution of genetically different cell populations within one tumour [14][15][16] .…”
mentioning
confidence: 99%
“…In contrast, the recent development of new methods for the comprehensive study of the single cell genome [13][14][15][16] , epigenome 17 and transcriptome 18 is leading to a new understanding of cellular diversity. For instance, the study of single breast cancer cells revealed a significant number of de novo DNA copy number changes that appeared after only one cell cycle 15 and the analysis of large numbers of single cells has provided interesting insight in the evolution of genetically different cell populations within one tumour [14][15][16] . In the field of hiPSC, a recent study described low-grade mosaicism in neurons and differentiated hiPSCs at high resolution using array-based comparative genomic hybridization (aCGH) and single-cell sequencing 19 .…”
mentioning
confidence: 99%
“…To determine the accuracy of copy-number profiling, we computed the distances between (1) the a priori known t(1;16) translocation breakpoint on chromosome 16 of family PGD004, which was determined to base resolution using single-cell paired-end sequencing and further validated by Sanger sequencing, 20 and (2) the copy-number breakpoints-that result from the unbalanced inheritance of the derivative chromosomes of t(1;16)-detected in the single blastomeres after siCHILD analysis of the SNP logR values.…”
Section: Module 2: Single-cell Haplarithmisismentioning
confidence: 99%
“…This is because the underlying copy-number state of the SNP is ignored and because the abundant WGA artifacts in single-cell assays produce false homozygous and heterozygous SNP calls. 13,14 Various methods for DNA copy-number profiling of single cells have been developed and rely on transforming probe intensities of microarrays 3,10,[15][16][17] or next-generation sequence read counts [18][19][20][21] into DNA copy numbers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation